Preparation and Properties of Carbon Nanofiber Modified Emulsified Asphalt Based on Ultrasonication and Surfactant and the Impact of SBR and NH4Cl - Liu, Xuhang; An, Yuning; Feng, Jinyan; Zhu, Xingyi; Li, Feng (Frontiers in Materials, 2020)
Carbon nanofiber (CNF) is a nanomaterial with unique mechanical properties, which can improve the properties of composite materials effectively. Types of research focused on the impact of CNF on asphalt, asphalt binder, and mixture. Traditional emulsified asphalt presents a limited performance at both high and low temperature. Meanwhile, emulsified asphalt with better performance is required in engineering. Referring to the research of CNF-asphalt, CNF is considerable to improve the performance of emulsified asphalt. In this study, a preparation method for CNF modified emulsified asphalt with styrene-butadiene rubber (SBR) was proposed. Ultrasonication and surfactant were utilized to disperse the CNFs in water. The optimum dispersion surfactant percentages and ultrasonic energy density to disperse CNFs were determined through ultraviolet-visible spectra (UV-vis spectra). The modified emulsified asphalt was produced using CNFs suspension with SBR as a modifier, and the properties of the residue with different percentages of CNFs were tested. Gel permeation chromatography (GPC) was performed to analyze the molecular size distribution. The results indicated that CNFs improved high-temperature performance of the residue significantly but decreased low-temperature properties. The addition of SBR not only perfected storage stability but also improved low-temperature performance by introducing more small molecules.